2009
DOI: 10.1080/00423110802339792
|View full text |Cite
|
Sign up to set email alerts
|

Rotational vibration absorber for the mitigation of rail rutting corrugation

Abstract: Torsional vibrations of metro wheel sets are known to be involved in the wavelength-fixing mechanism of the rutting-type rail corrugation. In the first part of this paper, the basic conditions for this type of wear to appear are established using a theory developed in the frequency domain. The efficiency of a dynamic vibration absorber tuned to the first torsional resonance of the wheel set to mitigate rutting corrugation is evaluated numerically. In the second part, the phenomenon is studied on a quarter-scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…Finally, the model does not include brake disks or gears and will not represent torsional vibrations. Torsional wheelset vibrations have been considered as a cause of corrugation at curves [1,39,40]; however, recent research [41] has shown that torsional wheelset vibrations are not correlated with corrugation development at curves. Torsional vibration is also considered in [42] for corrugation related to vibration up to about 100 Hz.…”
Section: Corrugation Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the model does not include brake disks or gears and will not represent torsional vibrations. Torsional wheelset vibrations have been considered as a cause of corrugation at curves [1,39,40]; however, recent research [41] has shown that torsional wheelset vibrations are not correlated with corrugation development at curves. Torsional vibration is also considered in [42] for corrugation related to vibration up to about 100 Hz.…”
Section: Corrugation Modelmentioning
confidence: 99%
“…This global perspective of the consistency conditions that govern the evolution of short pitch corrugation represents a novel contribution. The literature has so far only considered the effects of the vertical, lateral and torsional modes [1,3,39,40,56,57]. In [42], the relative longitudinal vibration of the two rails of a track is considered for corrugation initiation, for which each half track is modelled as an inertia, and longitudinal vibration modes of the rail as a flexible body are not considered.…”
Section: Analysis Of Longitudinal and Vertical Rail Modesmentioning
confidence: 99%
“…Because of great lateral forces and unsprung masses, the seizure of the surfaces will also be great and the irrupture will occur instantly, which leads to the generation of vibrations (Fig. 2), causing various kinds of surface destruction [5]. For the rail head-wheel tread contact, the sliding velocity and the contact pressure is about 0.1 m/sec and 1.5 GPa, respectively, but for the rail gauge-wheel flange the maximum sliding velocities reach 0.9 m/sec, and the maximum contact pressure was observed up to 2.7 Gpa [6].…”
Section: Peculiarities Of the Movement And Damageability Of The Wheelmentioning
confidence: 99%
“…In such conditions the wavelength is approximately 100-200 mm, which, at a movement speed approximately 100 km/h, corresponds to a relatively low frequency-50 Hz. The relatively high frequencies (up to 50 kHz) take place in the contact of the wheel flange and rail gauge at the stick-slip movement [7,8]. The periodic advancement of the inner wheel at the movement of the wheel-set in the curve causes the torsion deformations of the wheel-set shaft along with its bending deformations that can lead to the crack propagation in the places of location of wheels and gears (Fig.…”
Section: Peculiarities Of the Movement And Damageability Of The Wheelmentioning
confidence: 99%
“…After the optimization of the suspension parameters he achieved only 7% improvement because a dynamic absorber (DA) is capable to reduce the vibration only in a narrow frequency range. According to Collete [2] applying a solo DA will reduce the maximal amplitude of displacement in the resonance range. Therefore for reducing vibration in a wider frequency range there is necessary to use more DAs like is shown in work [3].…”
Section: Introductionmentioning
confidence: 99%